Perancangan Sistem Informasi Pengelolaan Surat Masuk dan Surat Keluar pada Kantor Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Sarolangun - Nur Hadiza; Widya Novita Sari; Hery Afriyadi (Departement of Mathematics Education, 2023)
Letters are media in communicating and as evidence of an event. The obstacle that occurs when using letters in physical form is good management so that letters are not easily lost or damaged. The management of incoming and outgoing letters at the Population Control and Family Planning Office still uses the conventional method, which means storing letters and data in the form of sheets of paper arranged in stacks. It can cause loss or damage to the paper and the search for letters takes a long time. To overcome these problems, we need an information system that can manage incoming and outgoing mail. The purpose of creating an information system for managing incoming and outgoing mail at the Population Control and Family Planning Office is to be able to manage mail data so that it is organized and can help make it easier for staff to work.